PENGARUH ARUS KAS DAN MODAL KERJA TERHADAP TINGKAT PROFITABILITAS - Pangartiningsih, Siammi; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this company is to obtain maximum profit for the company sustainability. The financial manager is appointed to how to obtain profit as maximum as possible in order to fulfill the need of the company. Therefore, the financial manager requires the information of cash flow and the work capital of the company in order to assess and to generate profit for the company. This research is conducted to analyze the influence of cash flow and work capital to the profitability.The secondary data which is the financial statement of the wholesale and retail trade companies which are listed in Indonesia Stock (IDX) in 2010-2012 periods are used as the research data. The purposive sampling has been used as the sample collection technique 12 companies have been selected as samples. The multiple linear regressions are used as the data analysis technique that is preceded by classic assumption tests which consist of normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test.The goodness of fit test of cash flow model and working capital is feasible as explanatory variable of profitability. The hypothesis test shows that cash flow does not have any significant influence to the profitability whereas the working capital has significant influence to the profitability.Keywords: Cash Flow, Working Capital, Profitability.